Transformasi Sosial Dalam Modernisasi Masyarakat Dusun Rondaman Melalui Program KKN: Pendekatan Pendidikan, Lingkungan, Dan Agama - Dedi Irwan Saujana Daulay; Dedi Saputra Tinambunan; Irwan Syaputra; Listi Hani Siregar; Nur Hidayah Hsb; Nur Sakilah; Purnama Meylandari; Putri Yani; Regina May Putri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Implementing Real Work Lectures (KKN) is a course that every student in higher education must take to provide understanding through the education, training and guidance process in order to be able to develop capacity and capability in managing the potential to develop the community environment. KKN activities will be carried out on July 4 – August 22 2023 in stages starting from the formation of environmental observation groups, debriefing and release. The programs that have been implemented are an indication of the success of all parties involved in the KKN group. The implementation of the KKN program is carried out by students in collaboration with NNB Dusun Rondaman, both of whom have a role in bringing about change for the better. The group 33 KKN team carries out service by providing education as a form of applying the knowledge they have gained to improve human resources in Rondaman Hamlet.